2011
DOI: 10.1029/2010pa001924
|View full text |Cite
|
Sign up to set email alerts
|

Environmental versus biological controls on Mg/Ca variability in Globigerinoides ruber (white) from core top and plankton tow samples in the southwest Pacific Ocean

Abstract: [1] Laser ablation inductively coupled plasma mass spectrometry was used to analyze the individual chambers from tests of foraminiferal fossil and plankton tow Globigerinoides ruber from the southwest Pacific Ocean, from latitudes 3°S to 42°S. The variability of Mg/Ca between chambers of an individual (intraindividual) and individuals of the same population (interindividual), is such that when converted to temperature, the extent of intra-individual and interindividual variability appears to exceed that attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 93 publications
7
48
0
Order By: Relevance
“…5). Within each shell, Mg/Ca ratios generally decrease in subsequent chambers, consistent with previous studies (Anand and Elderfield, 2005;Bolton et al, 2011). There is an average 31% reduction in Mg/Ca observed between the penultimate and final chamber, nearly identical to what is seen in G. bulloides tests from the southwest Pacific Ocean (Marr et al, 2011).…”
Section: La-icpmssupporting
confidence: 77%
See 2 more Smart Citations
“…5). Within each shell, Mg/Ca ratios generally decrease in subsequent chambers, consistent with previous studies (Anand and Elderfield, 2005;Bolton et al, 2011). There is an average 31% reduction in Mg/Ca observed between the penultimate and final chamber, nearly identical to what is seen in G. bulloides tests from the southwest Pacific Ocean (Marr et al, 2011).…”
Section: La-icpmssupporting
confidence: 77%
“…the development and calibration of this proxy have come from laboratory culture, sediment traps, plankton tows and core-tops, and nearly all regions of the world's oceans. Consistent throughout all of these calibration studies is an exponential Mg/Ca ratio:temperature sensitivity of 8-10% change in ratio per • C (Anand et al, 2003;Bolton et al, 2011;Dekens et al, 2002;Lea et al, 1999;Martínez-Botí et al, 2011;Mashiotta et al, 1999;McConnell and Thunell, 2005;Regenberg et al, 2009). The influences of secondary factors such as salinity and carbonate chemistry are still being evaluated, and in many cases appear to be species -and/or regionspecific (Arbuszewski et al, 2010;Dekens et al, 2002;Evans et al, 2016;Hertzberg and Schmidt, 2013;Hönisch et al, 2013;Kısakürek et al, 2008;Russell et al, 2004).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In addition, material from sediment traps in the Cariaco Basin was used to further test for biases introduced during sedimentation. This array of sites covered as broad a range of in situ d 11 B borate as possible for regions inhabited by G. ruber, and serves to test for regional variations (as seen in Mg/Ca, Bolton et al, 2011) that might stem from genotype differences (Darling and Wade, 2008). The locations of these core-top and sediment trap sites are shown in Fig.…”
Section: Samplingmentioning
confidence: 99%
“…In both cases a different calibration is needed to convert individual layer Mg/Ca to temperature. Additionally, Bolton et al (2011) have shown that for G. ruber Mg/Ca temperature calibrations differ for individual chambers. The choice of a particular calibration can thus not be justified in the absence of independent determination of the depth of formation of both layers.…”
Section: Implication For Paleotemperature Estimatesmentioning
confidence: 99%